Analysis of the Resilience of the Merah Putih Village Cooperative from the Perspective of Maqashid al-Sharia Amid Global Economic Dynamics - Sri Rahayu; R. Ilfan Muhammad; Dewi Fatmasari; Aan Jaelani (JURNAL ECONOMINA, 2026)
The Village Merah Putih Cooperative is a flagship program of the Indonesian government launched through Presidential Instruction Number 9 of 2025 to strengthen economic resilience at the village level. This study analyzes the resilience of the cooperative from the perspective of Maqashid Syariah amid global economic dynamics characterized by commodity price fluctuations, geopolitical tensions, and recession threats. Using a qualitative descriptive approach and literature study, this research finds that the five elements of Maqashid Syariah preservation of religion (hifz al-din), life (hifz al-nafs), intellect (hifz al-aql), lineage (hifz al-nasl), and property (hifz al-mal) provide a robust conceptual framework for the cooperative’s sustainability. The results indicate significant potential for improving financial inclusion and food security, although governance and digital adaptation challenges remain. This study recommends strengthening Sharia principles in cooperative operations to serve as a resilient model of people’s economy.